Design and analysis of p-cycle-based fault-restorable optical networks with multicast capability - Zhang, Feng (2009)
With recent advancement in optical transmission technology, WDM networks are able to offer huge capacity to meet the exponentially increasing demand. However, because network failures are capricious, without an efficient and fast recovery mechanism, they can cause huge data loss and therefore lead to severe disruption to network services and calamitous loss to end users. Hence, survivability is crucial to WDM networks carrying huge amount of unicast and multicast traffic. Compared with unicast traffic, multicast traffic suffers even more in a network failure. If a link/node in a multicast session fails, the traffic to all the downstream destinations of the failed link/node will be affected as well. In the past, extensive research has been directed to unicast traffic protection, due to its predominance. Recently, due to the rapid growth of multicast applications, such as video-conferencing, high definition television (HDTV), distance learning, multi-player on-line gaming, and so on, the problem of multicast traffic protection has started to draw more and more research interests. To our best knowledge, the preconfigured protection cycle (p-cycle) based approaches, which have been intensively studied for unicast traffic protection, have not been investigated for multicast traffic protection yet. Thus, motivated by the impact of the network failures to the optical multicast traffic and the merits of p-cycles, this thesis focuses on development and investigation of p-cycle based protection approaches for optical multicast traffic protection. The link-protecting p-cycle based approach for multicast traffic protection against link failure is analyzed first. The link protecting p-cycle based protection approach is shown to offer much better performance, compared with all other approaches. In particular, the joint optimization algorithm of p-cycle based link protection proposed achieves the best capacity efficiency among all algorithms for link failure recovery of static multicast traffic. For link failure recovery of dynamic multicast traffic, the dynamic p-cycle algorithm proposed achieves the lowest blocking probability; whereas the p-cycle based protected working capacity envelope algorithm offers the fastest computational speed. However, the link-protecting p-cycle based approach cannot handle node failure recovery.